2010
DOI: 10.1037/a0020105
|View full text |Cite
|
Sign up to set email alerts
|

Defining the boundary: Age-related changes in childhood amnesia.

Abstract: Childhood amnesia refers to the inability of adults to recall events that occurred during their infancy and early childhood. Although it is generally assumed that children and adolescents also experience childhood amnesia, with limited exceptions, most empirical research on the phenomenon has focused exclusively on adults. Here, we developed a new Timeline procedure to directly compare the early memories reported by children, adolescents, and adults. Overall, the proportion of memories reported before the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
93
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 79 publications
20
93
1
1
Order By: Relevance
“…A similar pattern of results-that older children remember for longer than younger children-has been observed across several tasks, including deferred imitation (Barr et al 1996;Herbert and Hayne 2000;Carver and Bauer 2001;Bauer 2007), visual paired comparison (Fantz 1956;Herbert and Hayne 2000;Hayne 2006a,b, 2011), and autobiographical memory (Ornstein et al 1997;van Abbema and Bauer 2005;Tustin and Hayne 2010) tests. Together, these findings converge to show that, although young children can acquire memories, they forget faster than older children.…”
Section: Older Children Remember Longersupporting
confidence: 49%
“…A similar pattern of results-that older children remember for longer than younger children-has been observed across several tasks, including deferred imitation (Barr et al 1996;Herbert and Hayne 2000;Carver and Bauer 2001;Bauer 2007), visual paired comparison (Fantz 1956;Herbert and Hayne 2000;Hayne 2006a,b, 2011), and autobiographical memory (Ornstein et al 1997;van Abbema and Bauer 2005;Tustin and Hayne 2010) tests. Together, these findings converge to show that, although young children can acquire memories, they forget faster than older children.…”
Section: Older Children Remember Longersupporting
confidence: 49%
“…Two studies have revealed age-cohort effects within childhood, such that the age of earliest memory is earlier for younger children relative to older children. For example, in Tustin and Hayne (2010) the average age of earliest memory among 5-year-old children was 1.7 years, whereas the average age of earliest memory among 12-to 13-year-old children was 2.5 years. Similarly, in Peterson et al (2005), the average age of earliest memory among 6-to 9-year-old children was 3 years, whereas the average age of earliest memory among 10-year-olds was 3.5 years.…”
Section: The Vulnerability Of Memory Traces Declines Over Developmentmentioning
confidence: 98%
“…Early reports involving child subjects were retrospective-they asked what was retained from childhood, but not what was lost. As a result, though the possibility that memory trace vulnerability was part of the explanation of childhood amnesia had been implicated theoretically (Bauer, 2007(Bauer, , 2008Olson & Newcombe, 2014;Peterson, Warren, & Short, 2011;Tustin & Hayne, 2010), there has been little opportunity to evaluate its role empirically.…”
Section: The Vulnerability Of Memory Traces Declines Over Developmentmentioning
confidence: 99%
“…Overall, a large body of research suggests that the grand average of the age reported in first memories is 3.5 years across multiple studies (Tustin & Hayne, 2010).…”
mentioning
confidence: 99%